Prevalence and predictors of medication-related emergency department visit in older adults: A multicenter study linking national claim database and hospital medical records - Park, Soyoung; Kim, A Jeong; Ah, Young-Mi; Lee, Mee Yeon; Lee, Yu Jeong; Chae, Jungmi; Rho, Ju Hyun; Kim, Dong-Sook; Lee, Ju-Yeun (Frontiers in Pharmacology, 2022)
Objectives: Older adults are more likely to experience drug-related problems (DRP), which could lead to medication-related emergency department visits (MRED). To properly evaluate MRED, the entire history of drug use should be evaluated in a structured manner. However, limited studies have identified MRED with complete prescription records. We aimed to evaluate the prevalence and risk factors of MRED among community-dwelling older patients by linking national claims data and electronic medical records using a standardized medication related admission identification method. Methods: We included older patients who visited the emergency departments of four participating hospitals in 2019. Among the 54,034 emergency department (ED) visitors, we randomly selected 6,000 patients and structurally reviewed their medical records using a standardized MRED identification method after linking national claims data and electronic medical records. We defined and categorized MRED as ED visits associated with adverse drug events and those caused by the underuse of medication, including treatment omission and noncompliance and assessed as having probable or higher causality. We assessed preventability using Schumock and Thornton criteria. Results: MRED was observed in 14.3% of ED visits, of which 76% were preventable. In addition, 32.5% of MRED cases were related to underuse or noncompliance, and the rest were related to adverse drug events. Use of antipsychotics, benzodiazepines, anticoagulants, traditional nonsteroidal anti-inflammatory drugs without the use of proton pump inhibitors, P2Y12 inhibitors, insulin, diuretics, and multiple strong anticholinergic drugs were identified as predictors of MRED. Conclusion: One in seven cases of ED visits by older adults were medication related and over three-quarters of them were preventable. These findings suggest that DRPs need to be systemically screened and intervened in older adults who visit ED.